ISSR BASED GENOTYPIC DIFFERENTIATION OF GRAPE (VITIS VINIFERA L.) - R. S. CHOUDHARY; V. S. ZAGADE; MABOODURRAHMAN; G. D. KHALAKAR (The Bioscan, 2014)
In order to study the genetic variability of four grape cultivars (Nanasaheb purple, Sonaka, Thompson seedless and Ganesh), 10 ISSR primers were screened of which seven were found polymorphic. These polymorphic primers produced a sum total of 86 bands of which 56 were polymorphic. The grape cultivars grouped into two major clusters at 51 per cent similarity. The first cluster had only Nanasaheb purple whereas; the second cluster contained Sonaka, Thompson seedless and Ganesh cultivars. Thompson seedless and Ganesh in the second cluster showed a similarity coefficient of 0.63. Clustering was strongly supported by high bootstrap values. Resolving power of the ISSR primers ranged between 3 (UBC 850) and 10 (UBC 810), PIC value from 0.78 (UBC 850) to 0.88 (UBC 811, UBC 815 and UBC 834), and Marker indices (MI) from 3.89 (UBC 850) to 8.80 (UBC 815 and UBC 834) with a mean value of 6.14, 0.85, and 6.88, respectively. The results revealed that ISSR could be a better tool for evaluation of genetic diversity among the grape cultivars.